2016
DOI: 10.3758/s13415-016-0448-x
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in white matter microstructure predict semantic control

Abstract: In everyday conversation, we make many rapid choices between competing concepts and words in order to convey our intent. This process is termed semantic control, and it is thought to rely on information transmission between a distributed semantic store in the temporal lobes and a more discrete region, optimized for retrieval and selection, in the left inferior frontal gyrus. Here, we used diffusion tensor imaging in a group of neurologically normal young adults to investigate the relationship between semantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 80 publications
2
27
0
Order By: Relevance
“…Dorsal tracts in the left hemisphere were shown to predict phonological skills (Saygin et al, 2013;Yeatman et al, 2011), while ventral tracts were broadly associated with access to meaning (Nugiel et al, 2016;Sarubbo et al, 2015) as well as with reading ability (Cummine et al, 2015;Ozernov-Palchik et al, 2019;Vandermosten et al, 2012;Yeatman et al, 2012a). However, it remains an open question whether these white matter tracts can be mapped onto specific language processes across stimulus and response modality, such as reading, listening and speaking.…”
Section: Introductionmentioning
confidence: 99%
“…Dorsal tracts in the left hemisphere were shown to predict phonological skills (Saygin et al, 2013;Yeatman et al, 2011), while ventral tracts were broadly associated with access to meaning (Nugiel et al, 2016;Sarubbo et al, 2015) as well as with reading ability (Cummine et al, 2015;Ozernov-Palchik et al, 2019;Vandermosten et al, 2012;Yeatman et al, 2012a). However, it remains an open question whether these white matter tracts can be mapped onto specific language processes across stimulus and response modality, such as reading, listening and speaking.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of individuals with semantic dementia or aphasia have implicated the UF in semantic retrieval (Harvey et al 2013; Han et al 2013), while other studies using electrical stimulation during neurosurgery suggest that the UF plays little to no role in semantic retrieval (Duffau et al 2009) or only plays a role in retrieving proper names and unique entities (Mehta et al, 2016; Papagno et al, 2014). In a prior study, we found no relationship between microstructure of the UF and performance on a semantic retrieval task (Nugiel et al 2016). Nevertheless, there is one semantic memory task that is consistently associated with the UF: proper name retrieval (Papagno et al 2011; Nomura et al 2013).…”
Section: Discussionmentioning
confidence: 66%
“…That would explain the current finding that structural integrity of the IFOF, and not the NAcc-VTA pathway, was associated with memory for highvalue words in older adults. Consistent with this suggestion, recent work has proposed that the IFOF is the primary tract responsible for processing of semantic information, with the UF typically playing a more supplementary role (Duffau et al, 2013;Nugiel et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…This semantic network appears to be largely left-lateralized (de Zubicaray et al, 2011;see Patterson et al, 2007 for a review), particularly when supporting the encoding and retrieval of verbal stimuli (Rice et al, 2015). The IFOF has been shown in prior DTI studies to be involved in both the retrieval (de Zubicaray et al, 2011) and control of semantic information (Nugiel et al, 2016), a conclusion further supported by lesion research (Harvey and Schnur, 2015) and examinations of functional connectivity (Turken and Dronkers, 2011). Additionally, many of the brain regions showing increased activity during encoding of high-value items in the present task, relative to encoding of low-value items, are connected via the IFOF.…”
mentioning
confidence: 99%